The challenge of diagnosing and treating bladder câncer (Research, Society and Development, 2022)
Introduction: Bladder cancer is the ninth most common neoplasm worldwide. It is a diverse disease with different outcomes related to its underlying basic biology, responsiveness to therapy, and host-related factors. Established risk factors for bladder cancer include male gender, older age, white race, occupational exposure to certain chemicals, pelvic radiation, use of medications such as cyclophosphamide, chronic bladder infection/irritation, personal or family history of bladder cancer, and smoking. Method: The search platform on the following sites: SciELO, Google academic, International Brazilian Journal of Urology, The Journal of Urology, PUBLAB and PUBMED. Outcome and Discussion: As a result, the spectrum of disease ranges from a relatively benign entity that is more troublesome than anything else to a lethal variant with great metastatic potential. For these reasons, early detection, markers of disease progression, and good surgical and medical therapies are paramount to impacting its natural history. Over the past 30 years, advances in endoscopic and surgical technique, along with discoveries in immunotherapy and chemotherapy, have resulted in substantial improvements in the care of patients with this disease. Conclusion: In this literature review, we highlight recent findings that establish a new and emerging standard of care for the treatment and diagnosis of patients with bladder cancer. As bladder cancer recurrence and mortality rates are high, research is needed to find suitable biomarkers for early detection, assessment of prognosis, and surveillance of drug responses.